Liquid fermentation method for producing salt-tolerant cellulase from sea aspergillus niger - YAO SHANJING; LIU JIEFENG; LIN DONGQIANG; XUE DONGSHENG (2011)
The invention discloses a liquid fermentation method for producing salt-tolerant cellulase from sea aspergillus niger. The liquid fermentation method comprises the following steps: 1) screening soil in 10-20m depth of coastal area of the East China Sea to obtain a strain of sea aspergillus niger; 2) inoculating the sea aspergillus niger into a PDA (potato dextrose agar) culture medium, culturing at 32-40 DEG C for 60-90 hours to obtain slant spores, and preserving the slant spores at 4 DEG C; 3) inoculating the slant spores on a PDA-1 culture medium, and culturing at 32-40 DEG C for 60-90 hours to obtain activated spores; 4) inoculating the activated spores on a slant of an eggplant bottle, and culturing at 42 DEG C for 74 hours to obtain eggplant bottle slant spores subject to expanding culture; and 5) utilizing sterile artificial sea water to dilute the eggplant bottle slant spores obtained by expanding culture to 108 spores/ml, inoculating on a liquid fermentation enzyme productionculture medium, and ferme